Runaway slaves, rock art and resistance in the Cape Colony, South Africa. Issue 4 (1st October 2020) - Sinclair-Thomson, Brent; Challis, Sam
ABSTRACT: The protracted colonisation of southern Africa's Cape created conditions of extreme prejudice and violence. Slaves, the unwilling migrants to the Cape, comprised a mixed group of individuals from the Dutch and British colonies: people with Malay, Malagasy, East and West African heritages. They combined to form the labour force for the colonial project, along with indigenous Khoe-San trafficked within an illegal domestic unfree labour economy. Escaped or 'runaway' slaves joined forces with groups of ' skelmbasters ' (mixed outlaws), who themselves were descended from San-, Khoe- and Bantu-speaking Africans (hunter-gatherers, herders and farmers). Together, they mounted a stiff resistance that held up the colonial advance for many decades from the late eighteenth century until the mid-nineteenth century. Engaging in guerilla-style warfare, they raided colonial farms for livestock, horses and guns. The ethnogenesis of such raiding bands is increasingly coming to the attention of archaeologists encountering the images they made of themselves in rock shelters, as well as the spiritual beliefs that they held in connection with escape and protection. The 'reverse' or 'entangled gaze' provided by this painted record gives us the perfect opportunity to view something of the slave and indigenous resistance from outside the texts of the colonial written record.